Evaluating the Causal Effects of TIMP-3 on Ischaemic Stroke and Intracerebral Haemorrhage: A Mendelian Randomization Study - Xiao, Linxiao; Zou, Xuelun; Liang, Yan; Wang, Yuxiang; Zeng, Lang; Wu, Jianhuang (Frontiers in Genetics, 2022)
Abstract Aim: This paper aimed to explore the causal role of tissue inhibitors of matrix metalloproteinase 3 (TIMP-3) in the risk of ischaemic stroke and intracerebral haemorrhage via Mendelian Randomisation (MR) study. Methods: The summary-level data of TIMP-3 were acquired from the KORA (Cooperative Health Research in the Region of Augsburg)-gen public database and the outcome of ischaemic stroke and intracerebral haemorrhage were obtained from genome-wide association studies conducted by MEGASTROKE and the International Stroke Genetics Consortium respectively. Five methods including inverse-variance weighting, weighted-median analysis, MR-Egger regression, MR Pleiotropy RESidual Sum and Outlier test, and MR-Robust Adjusted Profile Score were used to assess the causal role of TIMP-3 in the occurrence of ischaemic stroke and intracerebral haemorrhage. While the results from all the above methods were evaluated, inverse-variance weighting was defined as the main method for assessing causality. Heterogeneity and pleiotropic tests were utilised to evaluate the reliability of this study. Results: We found that TIMP-3 had a negatively causal relationship on the incidence of ischemic stroke (OR = 1.026, 95% CI: 1.007–1.046, p = 0.0067), especially for the occurrence of small vessel stroke (SVS; OR = 1.045, 95% CI: 1.016–1.076, p = 0.0024). We also found a weak negative relationship between TIMP-3 and the risk of cardioembolic stroke (CES; OR = 1.049, 95% CI: 1.006–1.094, p= 0.024). However, the causal corelation between TIMP-3 and intracerebral haemorrhage with its subtypes was statistically significant. Conclusion: Genetic evaluation revealed that high serum TIMP-3 levels is inversely associated with ischaemic stroke, SVS, and CES. The clinical indication of this finding warranties the underlying mechanism to be uncovered in the future.